2022
DOI: 10.3389/fnut.2022.1062671
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of antioxidant peptides from Moringa oleifera leaves and their protection against oxidative damage in HepG2 cells

Abstract: Moringa oleifera leaves are a kind of new food raw materials, rich in functional factors, M. oleifera leaves aqueous extract have antioxidant activity and M. oleifera leave protein is an important active ingredient in the aqueous extract. Numerous studies have shown that peptides have strong antioxidant activity. To reveal the antioxidant effects of M. oleifera (MO) leaves peptides, MO leave antioxidant peptides were isolated and prepared to clarify their antioxidant activity. MLPH1 (<1 kDa), MLPH3 (1~3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 45 publications
3
14
0
Order By: Relevance
“…After treatment with KP and KPH, the apoptosis rate of cells was significantly reduced, and the repair effect of KPH on cells was better than that of KP. This is similar to the results reported by Liang et al , 94 who showed that the antioxidant peptides from Moringa oleifera leaves separated using an ultrafiltration membrane have high antioxidant activity.…”
Section: Resultssupporting
confidence: 92%
“…After treatment with KP and KPH, the apoptosis rate of cells was significantly reduced, and the repair effect of KPH on cells was better than that of KP. This is similar to the results reported by Liang et al , 94 who showed that the antioxidant peptides from Moringa oleifera leaves separated using an ultrafiltration membrane have high antioxidant activity.…”
Section: Resultssupporting
confidence: 92%
“…It has been reported that antioxidant peptides could reduce oxidative stress by eliminating the ROS and enhance the antioxidant system of the cell . In this study, we found that two peptides, especially PG-7, could significantly eliminate the ROS and increase the activities of SOD, CAT, and GSH-Px in Ang II-induced HUVEC (Figures and ).…”
Section: Discussionmentioning
confidence: 55%
“…It has been reported that antioxidant peptides could reduce oxidative stress by eliminating the ROS and enhance the antioxidant system of the cell. 15 In this study, we found that two peptides, especially PG-7, could significantly eliminate the ROS and increase the activities of SOD, CAT, and GSH-Px in Ang II-induced HUVEC ( Figures 2 and 3 ). Our results demonstrated that peptides KA-8 and PG-7 protected the HUVEC from Ang II-induced injury through attenuating oxidative stress, which was also reflected in the improvement of the cell number and morphology after treatment with peptides ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 57%
“…Similarly, Fitriana [ 71 ] demonstrated a potent free radical scavenging activity with an IC 50 of 49.30 μg/mL in the DPPH assay using the methanolic extract of Moringa oleifera leaves, while we observed a value of 66.66 ± 0.53 μg/mL ( Table 3 ). Additionally, a significant antioxidant potential of peptides derived from M. oleifera leaves has been reported [ 72 ].…”
Section: Resultsmentioning
confidence: 99%